Effectiveness Of Posting Program on Adolescents' Knowledge About Stunting in Uteun Baya Village, Bandar Dua District, Pidie Jaya Regency: Efektivitas Program Posting Terhadap Pengetahuan Remaja Tentang Stunting di Desa Uteun Baya, Kecamatan Bandar Dua, Kabupaten Pidie Jaya - Asiah, Nur; Ilyas, Aiyub; Asnah Sihotang, Nur; Oktavinola Kaban, Febri (Universitas Haji Sumatera Utara, 2025)
Stunting is a condition where a child's body is lower than the average child of the same age due to nutritional deficiencies starting from the fetus or the child is growing. The lack of ability of parents to buy nutritious food during pregnancy and when the child is growing, along with the low education of the mother, the baby does not receive exclusive breastfeeding and the baby is born with a low birth weight are factors that cause children to experience stunting. The effect of stunting on the child's future is in the form of the child's physical appearance which looks shorter than children of the same age and the occurrence of cognitive, physical, language and sensory motor disorders. In Pidie Regency in the period of July 2022, there were 1,336 cases of stunting. The number of stunting cases in Pidie Jaya Regency was 37.8% and the number of health centers with the highest stunting rates was the Bandar Dua Health Center, namely in Uteun Baya Village. The purpose of the activity was to identify the effectiveness of the Program Tolak Stunting (POSTING) on adolescent knowledge about stunting. The location of the activity was in Uteun Baya Village, Bandar Dua District. Pidie Jaya, held in July - August 2024. The form of activity is health education. The number of participants is 29 people. The results of the activity obtained data that the majority of adolescent knowledge is good at 89.66%. This activity proves that the POSTING program can provide adolescents with an understanding of stunting. It is hoped that with the increase in adolescent knowledge, this can create a stunting-free family in Uteun Baya Village.